Transforming growth factor β can mediate apoptosis via the expression of TRAIL in human hepatoma cells - Herzer, Kerstin; Ganten, Tom M.; Schulze-Bergkamen, Henning; Koschny, Ronald; Krammer, Peter H.; Walczak, Henning (Hepatology, 2005)
Transforming growth factor β (TGF-β) has been shown to induce apoptotic cell death in normal and transformed hepatocytes. However, the exact mechanism through which TGF-β induces cell death is still unknown. We examined a potential role of various death receptor/ligand systems in TGF-β-induced apoptosis and identified the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) as a mediator of TGF-β-induced apoptosis in hepatoma cells. TGF-β-induced apoptosis is significantly impaired upon blockage of TRAIL. We show that TRAIL is upregulated in hepatoma cells upon treatment with TGF-β, whereas TRAIL receptor levels remain unchanged. In conclusion, our results provide evidence that the TRAIL system is critically involved in TGF-β-induced cell death in liver pathology.